Scalable camera traps for measuring the attractiveness of sugar baits for controlling malaria and dengue vectors - Felician C. Meza; Frank C. Tenywa; Simon Ashall; Fredros O. Okumu; Sarah J. Moore; Frederic Tripet (Parasites & Vectors)
Background Attractive targeted sugar baits (ATSBs) are promising new interventions that can complement existing vector control tools. However, reproducible and quantitative information on the level of attractiveness of ATSBs under field conditions is needed. Therefore, we customized camera traps for close-up imaging. We integrated them into a rugged ATSB monitoring station for day and nighttime recording of mosquitoes landing on the bait. Methods The camera traps were evaluated in a semifield system and then in the field in rural Tanzania. In semifield experiments, camera traps were set up in large cages (2 m × 5 m × 2 m) to record mosquitoes landing on an attractive sugar bait (ASB), a blank ASB, or 20% sucrose (w/v). Next, 198 mosquitoes (33 males and 33 females of Anopheles arabiensis, An. funestus and Aedes aegypti) were released into each large cage and allowed to seek a sugar meal for 72 h with a camera recording images of the mosquitoes present on the ASB at 1-min intervals. In the field, 16 camera traps were set in 16 households, 7 with ASB attractant, 7 with ASB blank, and 2 with 20% sucrose (w/v). Human landing catch (HLC) was performed on the same nights as the camera trap recordings. Results Under semifield conditions, significantly more mosquitoes visited the ASBs than the blank baits, with An. funestus visiting more frequently than An. arabiensis. There were no significant differences between female and male An. arabiensis visits, but female An. funestus visited more than their conspecific males did. The duration of visits did not vary between the ASB and blank controls or between the mosquito species. Moreover, mosquitoes visited the ASB or sucrose equally, with An. arabiensis visiting the baits more than An. funestus. Compared with male mosquitoes, female mosquitoes visited the baits more often. There was no significant difference in visit duration between the species.  In the field study, a mean of 70 An. arabiensis were caught per person per night on HLC, while 1 individual was caught per night on ASBs. There were significantly more visits by mosquitoes to the ASB than to the ASB blanks or sucrose solution, with more An. arabiensis visiting the baits than An. funestus or Culex quinquefasciatus. Significantly more females than males visited the baits of all the species. Again, the duration of visits was similar among An. arabiensis, An. funestus and C. quinquefasciatus. Aedes aegypti very rarely visited ASBs in the semifield experiments, and none were observed on baits in the field. Conclusions Using camera traps to record still images of mosquitoes on ASBs offers reliable, reproducible and quantitative information on their attractiveness in various environmental conditions. Thus, camera traps serve as effective tools for evaluating and improving ATSB technology. Graphical abstract